Palaeomagnetism of red beds of the Late Devonian Worange Point Formation, SE Australia - Thrupp, G. A.; Kent, Dennis V.; Schmidt, P. W.; Powell, C. McA. (1991)
Gently folded strata of the Late Devonian Merrimbula Group along the south coast of New South Wales are similar to numerous deposits of Late Devonian to Early Carboniferous, subaerial to shallow marine, quartzose sandstone that are known as the Lambie Facies of SE Australia. Because the Lambie sands overlap the early Palaeozoic tectonic elements of the Lachlan Fold Belt, large displacement since the Late Devonian of any Lachlan terranes, with respect to interior Australia, is precluded. We collected oriented core samples from 37 sites primarily in reddish, quartzose litharenites of the Worange Point Formation. The remanent magnetization is carried by haematite. Incremental thermal demagnetization reveals a dominant, well-defined, steep-upward-north component of magnetization that post-dates the mid-Carboniferous folding. The south pole position (146.4"E, 68.6"S, Ag5 3.1") derived from the overprinted specimens is close to both the Late Carboniferous and mid-Cretaceous reference poles as well as the spin axis of today. The overprint is attributed to both viscous partial thermoremanent and chemical remanent magnetization (VPTRM and CRM). Its exclusively normal polarity is consistent with a mid-Cretaceous acquisition, perhaps related to the rifting of the SE Australian margin.